Transformações na estrutura produtiva e no emprego da região metropolitana de João Pessoa - Lima, Jurandir dos Santos (2013)
This research, entitled "Transformations of Productive Structure and Employment in metropolitan area of João Pessoa", aimed to analyze the changes in the production structure and employment of such regional unit, with the intent to answer the following question: changes in the productive sectors of the economy, its labor market and formal employment occurred in this portion of space in the first decade of this century, were enough to change their economic structures? Regarding the analysis of the productive sectors, it is evident a low weighting in the sector of agriculture in total GDP of RMJP. As for the gross value added for the industry, comes in higher than the relative position of agriculture in GDP at current prices in the metropolitan area of João Pessoa. The service sector of the metropolitan area there is a growth and relative share higher than the sectors of agriculture and industry in terms of gross value added at current prices during the period under examination. The labor market in the metropolitan area of João Pessoa reveals significant evolution of persons employed, a higher education degree and a relevant transformation in its formal employment, and a redistribution of income from work, important for all classes, especially the benefits to the base of the pyramid. A breakdown of industrial and service sector reveal changes and / or stays in its productive structure, resulting in a better understanding of GDP fluctuations in the metropolitan area of João Pessoa.